2018
DOI: 10.1021/acs.inorgchem.8b00618
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Atom Noninnocence of a Tridentate [SNS] Pincer Ligand

Abstract: Double deprotonation of bis(2-mercapto-4-methylphenyl)amine ([SNS]H) followed by addition to NiCl(PR) in air-free conditions afforded [SN(H)S]Ni(PR) (1a, R = Cy; 1b, R = Ph) complexes, characterized as diamagnetic, square-planar nickel(II) complexes. When the same reaction was conducted with 3 equiv of KH, the diamagnetic anions K{[SNS]Ni(PR)} were obtained (K[2a], R = Cy; K[2b], R = Ph). In the presence of air, the reaction proceeds with a concomitant one-electron oxidation. When R = Cy, a square-planar, S = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 60 publications
2
39
0
Order By: Relevance
“…The H 2 evolution pathways of, e. g., pincer, thiosemicarbazone, and thiolate complexes are known to involve the redox‐active scaffold. Proton relay sites and redox‐active ligands are proposed to significantly enhance the kinetics of H 2 formation and decrease the HER overpotentials of metal complexes . However, a redox non‐innocent coordination environment also may result in non‐productive pathways .…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 evolution pathways of, e. g., pincer, thiosemicarbazone, and thiolate complexes are known to involve the redox‐active scaffold. Proton relay sites and redox‐active ligands are proposed to significantly enhance the kinetics of H 2 formation and decrease the HER overpotentials of metal complexes . However, a redox non‐innocent coordination environment also may result in non‐productive pathways .…”
Section: Introductionmentioning
confidence: 99%
“…1820 To this end, there has been a resurgence into redox-active, 20,21 hemilabile, 2327 and so called proton-responsive ligand scaffolds 2840 However, studies that incorporate the triad of redox-activity, hemilability, and proton responsivity, all in a single ligand scaffold, are exceedingly limited. 4147 Our group has been active in developing methodologies that control the movement of both protons and electrons for biologically relevant reactions by utilizing the redox-active pyridinediimine (PDI) scaffold merged with a proton-responsive secondary coordination sphere. 4850 Those preliminary studies successfully showed: 1) the PDI scaffold can be tailored to facilitate NO 2 − reduction, and; 2) the NO 2 − reduction is dependent on the protonation state of the secondary coordination sphere (proton-responsivity).…”
Section: Introductionmentioning
confidence: 99%
“…53 Synthetic systems where designed ancillary ligands can donate both protons and electrons have been an area of increasing interest. 4,23,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] However, leveraging this strategy for the biomimetic activation of O2 has not been explored. We reasoned that the previously reported pyrrole-based ligand scaffold tBu,Tol DHP ( tBu,Tol DHP = 2,5bis((2-t-butylhydrazono)(p-tolyl)methyl)-pyrrole, Scheme 1), which can donate two electrons and two protons to a substrate, would be an ideal scaffold to demonstrate this principle.…”
Section: Enzymaticmentioning
confidence: 99%